Venezuela - Díaz-Bonilla, Eugenio (2019)
Eugenio Diaz-Bonilla POLICY SEMINAR Technical Discussion on the 2019 Global Report on Food Crises: Working together to prevent food crises Co-Organized by IFPRI, FAO North America and Food Security Information Network (FSIN) APR 26, 2019 - 09:30 AM TO 11:00 AM EDT